The Essential Role of Social Support to Strengthening Resilience of Neglected Elderly in Environment of Social Residence - Wibisono, Putra; Nuha, Moch. Syihabudin; Laela, Faizah Noer (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The Essential Role of Support in Strengthening Resilience in Neglected Elderly in Social Shelters. The increase of elderly people in Indonesia is a new challenge in social welfare, especially for those who are abandoned without family support. Elderly people in neglected conditions will experience psychological pressure ranging from loneliness, helplessness, and loss of meaning in life, so that it can reduce their level of resilience in dealing with life. This research was conducted using a qualitative method through observation and in-depth interviews with the elderly at UPTD Liponsos Keputih Surabaya. This research aims to find out how the role of social support in shaping and increasing resilience in displaced elderly. The results showed that social support from peers has a positive impact on the resilience formation process. With intense social interaction, feelings of compatibility and involvement in joint activities, it can create a sense of acceptance, belonging, their self-esteem. Social support is proven to play an important role in building the resilience of displaced elderly and can be the preparation of policies and programs to improve the welfare of the elderly in the future